(untitled) (TSUL LEGAL REPORT, 2026)
This research, integral to the examination of foreign countries’ best practices in civil service reform and the enhancement of social guarantees for civil servants within our nation, employs a comprehensive set of research methods. The study aims to glean insights from the transformative experiences of countries undergoing radical public administration reform. Methodologically, a comparative analysis is employed to assess the strategies and policies in the field of public service. The research focuses on nations like Georgia, Estonia, Poland, Croatia, Vietnam, and Singapore, utilizing case studies and in-depth interviews with key stakeholders. The conclusions drawn from this research shed light on the effectiveness of various reform measures and their implications for civil service enhancement. The findings advocate for the adaptation of successful practices observed in the aforementioned countries. Moreover, the research suggests specific legislative adjustments to align our civil service framework with international best practices. The proposed legislative modifications aim to foster a more responsive, accountable, and efficient civil service, ultimately contributing to the overall development and well-being of our society.